The treatment of CML at an environment with limited resources. Issue 10 (25th November 2016) - Gómez-Almaguer, David; Cantú-Rodríguez, Olga G.; Gutiérrez-Aguirre, Cesar H.; Ruiz-Argüelles, Guillermo J.
Abstract : Objectives: This article reviews clinical experiences in the treatment of chronic myeloid leukemia (CML) in an environment of limited resources. Methods: We reviewed recent publications on Pub med and abstracts from mayor congresses relevant to the disease. Results: CML is a hematological neoplasm observed more frequently in adults, regardless of their socioeconomic status. Until recently, available treatments improved patients' quality of life but did not modify survival. It was not until interferon appeared that patients received a drug that reduced and even eliminated Philadelphia chromosome-positive (Ph+) cells. Discussion: With the start of the new millennium, the International Randomized Study of Interferon-α plus cytarabine versus STI571 (IRIS) trial demonstrated a dramatic improvement in survival by comparing imatinib versus interferon alpha plus cytarabine. The Food and Drug Administration (FDA) approved imatinib as first-line treatment for newly diagnosed CML in 2001 due to its outstanding effectiveness. Years later, three second-generation (dasatinib, nilotinib, bosutinib) and one third-generation (ponatinib) tyrosine-kinase inhibitors (TKIs) were developed and approved. These highly effective treatment options, however, are not affordable for many low-income patients. Additionally, the use of drugs that effectively treat but do not cure the disease has resulted in an important economic impact for patients and health care systems worldwide, especially those in developing countries. Imatinib is the least expensive and a very effective TKI in many low-income countries. Early allogeneic stem cell transplantation must be considered in the management of selected patients before CML transformation.